Treatment With Acetylsalicylic Acid Reverses Endotoxin Tolerance in Humans In Vivo: A Randomized Placebo-Controlled Study. Issue 4 (April 2019) - Leijte, Guus P.; Kiers, Dorien; van der Heijden, Wouter; Jansen, Aron; Gerretsen, Jelle; Boerrigter, Verin; Netea, Mihai G.; Kox, Matthijs; Pickkers, Peter
Abstract : Objective: To investigate immunostimulatory effects of acetylsalicylic acid during experimental human endotoxemia and in sepsis patients. Design: Double-blind, randomized, placebo-controlled study in healthy volunteers and ex vivo stimulation experiments using monocytes of septic patients. Setting: Intensive care research unit of an university hospital. Subjects: Thirty healthy male volunteers and four sepsis patients. Interventions: Healthy volunteers were challenged IV with endotoxin twice, at a 1-week interval, with each challenge consisting of a bolus of 1 ng/kg followed by continuous administration of 1 ng/kg/hr during 3 hours. Volunteers were randomized to acetylsalicylic acid prophylaxis (80 mg acetylsalicylic acid daily for a 14-d period, starting 7 d before the first endotoxin challenge), acetylsalicylic acid treatment (80 mg acetylsalicylic acid daily for the 7-d period in-between both endotoxin challenges), or the control group (receiving placebo). Furthermore, monocytes of sepsis patients were incubated with acetylsalicylic acid preexposed platelets and were subsequently stimulated with endotoxin. Measurements and Main Results: Acetylsalicylic acid prophylaxis enhanced plasma tumor necrosis factor-α concentrations upon the first endotoxin challenge by 50% compared with the control group ( p = 0.02) but did not modulate cytokine responses during the second endotoxin challenge. In contrast, acetylsalicylic acid treatment resulted in enhanced plasma levels of tumor necrosis factor-α (+53%; p = 0.02), interleukin-6 (+91%; p = 0.03), and interleukin-8 (+42%; p = 0.02) upon the second challenge, whereas plasma levels of the key antiinflammatory cytokine interleukin-10 were attenuated (–40%; p = 0.003). This proinflammatory phenotype in the acetylsalicylic acid treatment group was accompanied by a decrease in urinary prostaglandin E metabolite levels (–27% ± 7%; p = 0.01). Ex vivo exposure of platelets to acetylsalicylic acid increased production of tumor necrosis factor-α (+66%) and decreased production of interleukin-10 (–23%) by monocytes of sepsis patients. Conclusions: Treatment, but not prophylaxis, with low-dose acetylsalicylic acid, partially reverses endotoxin tolerance in humans in vivo by shifting response toward a proinflammatory phenotype. This acetylsalicylic acid–induced proinflammatory shift was also observed in septic monocytes, signifying that patients suffering from sepsis-induced immunoparalysis might benefit from initiating acetylsalicylic acid treatment. Abstract : Supplemental Digital Content is available in the text.